2020
DOI: 10.1021/acs.joc.9b03278
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)-Citreoisocoumarin, (−)-Citreoisocoumarinol, (−)-12-epi-Citreoisocoumarinol, and (−)-Mucorisocoumarins A and B Using a Gold(I)-Catalyzed Cyclization Strategy

Abstract: A unified and concise first asymmetric total synthesis of (−)-citreoisocoumarin (2), (−)-citreoisocoumarinol (3), 12-epi-citreoisocoumarinol (4), and (−)-mucorisocoumarins A (5) and B (6) have been accomplished from the common intermediate (−)-6-O-methyl-citreoisocoumarin (1). Central to the synthetic approach is a regioselective gold­(I)-catalyzed 6-endo-dig cyclization strategy for the construction of the isocoumarin skeleton. The other key steps in this approach included Sonogashira coupling, Tsuji-Wacker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…A key step in this synthesis is a Pd(0)-catalyzed cross-coupling reaction between an aryl triflate (4), which already contained the spacer arm, and an appropriately functionalized arylboronic acid (6) (Scheme 1). The aryl triflate 4 was prepared in two steps from the readily available 1,3-benzodioxinone 1 [21,22]. First, an O-alkylation reaction with methyl 5-bromovalerate was performed under standard Williamson ether synthesis conditions.…”
Section: Hapten Design and Synthesismentioning
confidence: 99%
“…A key step in this synthesis is a Pd(0)-catalyzed cross-coupling reaction between an aryl triflate (4), which already contained the spacer arm, and an appropriately functionalized arylboronic acid (6) (Scheme 1). The aryl triflate 4 was prepared in two steps from the readily available 1,3-benzodioxinone 1 [21,22]. First, an O-alkylation reaction with methyl 5-bromovalerate was performed under standard Williamson ether synthesis conditions.…”
Section: Hapten Design and Synthesismentioning
confidence: 99%
“…The spin system of H 2 -9/H-10/H 2 -11/H 2 -12/H 3 -13 in the 1 H- 1 H COSY spectrum ( Figure 2 ) as well as the HMBC correlations ( Figure 2 ) from H 2 -9 to C-3 and C-4 showed that the side chain was substituted at C-3. By comparing the specific rotation of 11 [[α]−21.5 (с 0.06, MeOH)] with (−)-citreoisocoumarin [[α] −29.8 ( с 0.34, MeOH)] ( Mallampudi et al, 2020 ), the 10 R configuration at C-10 in 11 was indicated. Thus, the gross structure of 11 was defined as shown.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, this methodology was reinvestigated by the same research group [44] in the context of total synthesis of other isocoumarin core containing natural product such as 6-O-Methyl-Citreoisocoumarin, which could be further served as an important key intermediate for the total synthesis of (À )-Citreoisocoumarin, (À )-Citreoisocoumarinol, 12-epi-(À )-Citreoisocoumarinol, (À )-Mucorisocoumar in A and (À )-Mucorisocoumarin B through simple synthetic manipulations (Scheme 23).…”
Section: Carbonyl Participation Of 22-dimethyl Benzo [D]-[13]dioxinmentioning
confidence: 99%